SOUTH AFRICA-RUSSIA RELATIONS THROUGH THE LENS OF BRICS: A STRATEGIC NEXUS IN A MULTIPOLAR WORLD - Prakash, Aditya (ShodhKosh: Journal of Visual and Performing Arts, 2022)
South Africa and Russia have witnessed significant transformation in their relations especially within the framework of the BRICS (Brazil, Russia, India, China, and South Africa). The very existence of both nations within this strategic grouping reflects their shared commitment towards disrupting the status quo, i.e. the dominance of the global affairs and institutions by the Western powers and forging ahead towards a shared commitment to reshape the global governance in a multipolar world order. South Africa has occupied a unique position within BRICS; it is the youngest member of the grouping, and has leveraged its geopolitical influence in the African continent and simultaneously has not shied away from aligning with Russia on critical global issues. This paper traces the evolution of South Africa – Russia relations, their intertwining and collaborative efforts within the BRICS framework that has challenged the paradigms of economic and political governance of the West. The paper will also highlight how BRICS as a platform has advanced South Africa and Russia’s economic cooperation, especially in sectors like energy and trade. It will also look into cooperation on climate change and how both countries have valued in expanding the intra-BRICS trade and investment vis-à-vis sectors like defence and mining. Their support to New Development Bank (NDB) and the Contingent Reserve Arrangement (CRA) in reducing dependency on financial institutions will also be investigated. The study will also focus on how the partnership between both countries will carve out broader implications for the regional and global dynamics. While South Africa acts as a gateway to African markets for Russia, Russia’s geopolitical clout helps South Africa to align itself with one of the most powerful states in the world. The relationship is not bereft with challenges though, as both countries have divergent domestic policies and Russia is embroiled in its war with the West. Finally, the paper will seek to situate South Africa – Russia relations within the context of BRICS for their shared vision of a better equitable global order, where their partnership and BRICS as a platform aims for global rebalancing and sustainable development.